Hak Waris Bagi Anak yang Lahir dari Perkawinan Campuran Menurut Perspektif Hukum Perdata Internasional - Tsabita Az Zahra; Berliana Clara Bella; Arsya Ghaniyyah Hariyadi; Dita Nadya Anastasya; Romadhoni Nova Karisma; Lutfi Robiatul Adawiyah; Fahmi Fairuzzaman (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
Mixed marriages raise several issues and have impacts related to legal relationships. Such as citizenship, marriage agreements, divorce issues, custody rights for children born in mixed marriages and inheritance rights for children arising from these marriages. This research uses a normative doctrinal approach. Because in concept this research is sourced from written norms. Therefore, the research is carried out through the analysis of laws and regulations related to inheritance rights for children who have been born from mixed marriages. Therefore, the study carried out is only “limited” to the (written) laws and regulations related to the object under study. The results show that children born from mixed marriages also have legal protection. The existence of universal citizenship principles contained in Law No. 12/2006 on citizenship, such as the principle of ius sanguinis; determining the citizenship of a child from his descendants; the principle of ius soli, determining the citizenship of the child from his birthplace; the principle of single citizenship, emphasizing that every child can only have one citizenship; and the principle of dual citizenship, providing dual citizenship for every child in accordance with the decision of the Act.